Teaching System Design of Art Design Major under the Background of Economic Management Mode Change - Jiaxin Zheng (Discrete Dynamics in Nature and Society)
With the development of digital technology, the curriculum design of art majors is also quite different from traditional courses. With the continuous development of information technology and the continuous maturity of campus network technology, teaching resources have become an important part of information resources. High-quality teaching resources play an important role in improving teaching quality and excavating educational development potential. However, traditional classroom teaching is difficult to meet people’s needs. In the context of the current new normal, the way of social and economic management has changed. On the one hand, traditional course teaching resources store information in the forms of paper lesson plans, PPT courseware, discrete pictures, and video files. These forms of storage are not conducive to the distribution and sharing of resources. On the other hand, these teaching resources are scattered among the teaching teachers. As the curriculum develops, the courses taught by teachers change. Because schools lack effective means for unified management, these teaching resources are easily lost. The used method is not conducive to the accumulation of teaching resources or the continuation and development of courses. In order to present good results, these materials usually occupy a large amount of storage space. Therefore, some existing information-based teaching platforms cannot meet the demand. We use network and web technology to develop a teaching file management system, which is very necessary. This paper firstly compares the mature teaching resource management system on the market and some problems in its professional application. Secondly, the article analyzes the actual situation of teaching resource management of art design majors in China and generally describes the system development background and technology. Then, the paper analyzes the requirements of the system in detail by using the object-oriented method and gives the overall design and implementation method of the system. These methods include the use case diagram of the subsystem, the flow chart of the main module, the system architecture, and the design and application of UML. Finally, this paper designs a test case for the teaching resource management system.